Penegakan Hukum Pidana Siber di Indonesia: Tantangan dan Solusi Era Digital - Rahmadiani, Utami (ARBITER: Jurnal Ilmiah Magister Hukum, 2026)
The acceleration of digitalization in Indonesia has led to a significant rise in cybercrime, posing serious threats to national digital sovereignty, while law enforcement agencies continue to face institutional capacity gaps in responding to the unique characteristics of cybercrime. This study aims to analyze the multidimensional challenges in cyber criminal law enforcement and to formulate strategic solutions that are responsive to the dynamics of contemporary digital crime. The research adopts a normative legal approach through a literature review of relevant legislation, legal doctrines, and official documents. Data analysis is conducted using a descriptive-analytical method, employing systematic, grammatical, and teleological interpretations, supported by a limited comparative approach to best practices in selected international jurisdictions. The findings indicate that cybercrime law enforcement is constrained by limited human resource capacity in digital forensics, weak inter-agency coordination, the volatility of electronic evidence, offender anonymity, and low public awareness of cybersecurity. Law Number 19 of 2016 provides a comprehensive legal framework; however, its implementation is hindered by the transnational nature of cybercrime that exceeds national jurisdiction. The study concludes that a holistic approach is required, including strengthening human resource capacity, standardizing digital forensic infrastructure, reinforcing adaptive regulations, developing a national cybersecurity ecosystem, and enhancing international cooperation. This research contributes an integrative analytical framework that supports the institutional capacity building needed to address increasingly complex digital crimes.